Continuous ovarian stimulation: a proof-of-concept study exploring the uninterrupted use of corifollitropin α in DuoStim cycles for enhanced efficiency and patient convenience (Alicante protocol) - Juan Carlos Castillo, M.D., Ph.D; Ana Fuentes, M.D; Jose Antonio Ortiz, M.Sc., Ph.D; Esther Abellán, M.Sc; Andrea Bernabeu, M.D., Ph.D; Rafael Bernabeu, M.D., Ph.D (Elsevier, 2024)
Objective: To explore the use of weekly continuous dosing of corifollitropin α in DuoStim cycles. Design: Pilot-matched case-control study. Setting: Private fertility center. Patient(s): Cases were defined as DuoStim cycles performed from November 2022 to May 2023 receiving weekly continuous dosing of corifollitropin α (n = 15). Controls were chosen from a database comprising DuoStim cycles conducted at our institution during the years 2021/2022. Matching was done on a 1-to-1 basis, based on antimüllerian hormone values (±0.4 pmol/L) and age (n = 15). Intervention(s): Injections of corifollitropin α once every 8 days, along with uninterrupted oral administration of micronized progesterone 200 mg/d (for luteinizing hormone surge prevention) throughout the follicular and luteal phases for ovarian stimulation. Oocyte retrieval. Main outcome measure(s): Total number of cumulus-oocyte complexes and metaphase II oocytes obtained in follicular + luteal phase stimulation. Secondary outcomes evaluated fertilization rates, number of blastocysts, days of stimulation, number of injectables required, and gonadotropin cost. Result(s): The study group achieved similar total oocyte and MII yield vs. daily follicle-stimulating hormone protocol (13.3 ± 6.9 vs. 11.8 ± 6.1 and 10.4 ± 6.3 vs. 9.2 ± 4.6, respectively). All secondary outcomes showed no significant differences. The study group experienced a significant reduction of injections to complete a DuoStim cycle (4.5 ± 1.4 vs. 35.2 ± 12.2; mean deviation -30.7; 95% confidence interval, −37.5- to −23.9)]. Conclusion(s): Corifollitropin α on a weekly basis throughout a DuoStim cycle yields an equivalent number of oocytes as standard daily follicle-stimulating hormone administration while drastically reducing the number of required injections. Trial registration number: NCT05815719. EudraCT: 2022-003177-32.